(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2012)
This case report represents assessment and management of a maxillary left first molar tooth containing five root canals by endodontic treatment. In this case Mesiobuccal 2 (MB2), Mesiopalatal (MP) and Distobuccal (DB) canals were missed as well as very poor obturation at palatal and mesiobuccal1(MB1) canal during previous treatment history. Three mesiobuccal (MB1, MB2, and MP), DB and palatal canals were identified and endodontic retreatment was done followed by final restoration. This case provides an evidence of variations in the root canals of the mesiobuccal root of maxillary first molar tooth. Complete clinical and radiographic examination and adequate knowledge of the morphology of this kind of teeth is necessary for successful clinical outcome. DOI: http://dx.doi.org/10.3329/bsmmuj.v5i1.11026 BSMMU J 2012; 5(1):61-64